2022
DOI: 10.3390/molecules27185777
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Palynological, Chemical, and Bioactive Properties of Non-Studied Bee Pollen and Honey from Morocco

Abstract: Bee products are known for their beneficial properties widely used in complementary medicine. This study aims to unveil the physicochemical, nutritional value, and phenolic profile of bee pollen and honey collected from Boulemane–Morocco, and to evaluate their antioxidant and antihyperglycemic activity. The results indicate that Citrus aurantium pollen grains were the majority pollen in both samples. Bee pollen was richer in proteins than honey while the inverse was observed for carbohydrate content. Potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…Similarly, the maximum levels of pinocembrin (19.775 µg/g) and pinobanksin (10.826 µg/g) were detected in Ea. Hesperetin, detected in Citrus HBP by Bakour et al (2022) at 488.9 mg/kg, had the highest values in Sin (4.815 µg/g) and Cc 2 (4.513 µg/g) in our study.…”
Section: Phenolic Compositionsupporting
confidence: 45%
See 2 more Smart Citations
“…Similarly, the maximum levels of pinocembrin (19.775 µg/g) and pinobanksin (10.826 µg/g) were detected in Ea. Hesperetin, detected in Citrus HBP by Bakour et al (2022) at 488.9 mg/kg, had the highest values in Sin (4.815 µg/g) and Cc 2 (4.513 µg/g) in our study.…”
Section: Phenolic Compositionsupporting
confidence: 45%
“…(2017) also detected kaempferol, myricetin, and quercetin in C. creticus HBP. The rutin content in HBPs from Türkiye and Morocco ranged from 25.59–692.85 µg/100 g to 182.4 ± 2.4 mg/kg, respectively (Bakour et al., 2022; Ulusoy & Kolayli, 2014). Rutin contents were found within these ranges, with the highest amount detected in Q.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Lamiaceae) [100]. A fact recently reconfirmed by Bakour et al [101], who showed that BP with 50% Citrus aurantium had the highest hesperidin content among PCs (488.90 µg/g BP), and also showed more potent antioxidant activity.…”
Section: Phenolic Compound Profiles By Uhplc-dad-esi/msmentioning
confidence: 67%
“…In honey bee, three phenolic compounds were characterized, these are; catechin, caffeic acid and vanillic acid; however, in bee pollens six phenolic compounds were identi ed, these are; hesperidin, cinnamic acid, apigenin, rutin, chlorogenic acid, and kaempferol. These compounds owe antioxidant, digestive, antimicrobial, immunostimulatory, nutraceutical, and growth promoting effects (Bakour et al, 2022). Daisa et al, (2013) found that rabbit diets supplemented with BP resulted in a higher conception rate, a lower number of service conception rates, a larger litter size, and higher milk production.…”
Section: Productive Performance Of Does and Offspring During Lactationmentioning
confidence: 99%